2014
DOI: 10.1116/1.4869059
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of anatase TiO2 films by atomic layer deposition and low annealing temperature

Abstract: In this paper, the authors studied anatase TiO2 films, fabricated by using atomic layer deposition and postdeposition annealing (PDA). The as-grown TiO2 films were of high purity; the carbon and nitrogen contents were within the x-ray photoelectron spectroscopy detection limit of 3–5 at. %. The anatase TiO2 film fabricated by PDA at 500 °C in O2 had a very high dielectric constant of >30 and was of high quality because it exhibited no hysteresis at its flatband voltage (Vfb) and contained negligible def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Figure The defect charges in the Al 2 O 3 and (Ta/Nb)O x films were also examined using the relationship between V fb and EOT high-k , as shown in Fig. 22 We confirmed that the Al 2 O 3 and (Ta/Nb)O x films were high quality because there were not charged. Here, there were three sources of charges: a sheet of charges (Q ss ) at the SiO 2 /Si interface, uniformly distributed charges (q ohigh-k ) in the high-k materials such as Al 2 O 3 and (Ta/Nb)O x , and a sheet of charges (Q IL ) at the high-k/SiO 2 interface in the Pt/high-k/ SiO 2 /Si stack structure.…”
Section: A Characteristics Of Al 2 O 3 and (Ta/nb)o X Filmssupporting
confidence: 52%
“…Figure The defect charges in the Al 2 O 3 and (Ta/Nb)O x films were also examined using the relationship between V fb and EOT high-k , as shown in Fig. 22 We confirmed that the Al 2 O 3 and (Ta/Nb)O x films were high quality because there were not charged. Here, there were three sources of charges: a sheet of charges (Q ss ) at the SiO 2 /Si interface, uniformly distributed charges (q ohigh-k ) in the high-k materials such as Al 2 O 3 and (Ta/Nb)O x , and a sheet of charges (Q IL ) at the high-k/SiO 2 interface in the Pt/high-k/ SiO 2 /Si stack structure.…”
Section: A Characteristics Of Al 2 O 3 and (Ta/nb)o X Filmssupporting
confidence: 52%
“…Thus, much of the research work is widespread on the application of thermodynamically metastable anatase phase. The deposition of titania by vacuum based processes are extensively investigated, but requires additional attention during the process [11][12][13][14]. Alternatively, solution based process is quite attractive, as titania can be obtained with high purity and chemical homogeneity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although this is usually a concern for nanoparticles, nanocrystalline particles could be formed in the ALD films. Nabatame et al [ 34 ] studied anatase TiO 2 films fabricated by using ALD and postdeposition annealing, and discussed the flat band voltage change caused by the bottom interface dipole as well as how the dipole relates to oxygen introduced into the TiO 2 layer during oxidation annealing. Few studies reported the effect of annealing on the properties of plasma or thermal ALD TiO 2 films.…”
Section: Introductionmentioning
confidence: 99%